Analisis Media Poster Capres Prabowo Sandi Dalam Kampanye Pilpres Tahun 2019 - Amelia Miranda; Adek Cerah Kurnia Azis (LPPM STIKI Malang, 2020)
This research was conducted because it was found to report a problem in the design of the presidential election campaign poster, for that research related to analyzing the design of the Prabowo-Sandi campaign poster in the Presidential Election (2019). Color, typography, layout on Prabowo-Sandi's design media poster in the 2019 presidential election campaign The research method uses descriptive qualitative by gathering information about the Prabowo-Sandi campaign poster posters in 2019. The sample in this study used a cluster random sampling sample using a sample of small unit groups. The results showed that Prabowo-Sandi's media poster design in the 2019 Presidential Election campaign received a good category with an average of 89 with good results.